Algebra 1

Published by Prentice Hall
ISBN 10: 0133500403
ISBN 13: 978-0-13350-040-0

Chapter 2 - Solving Equations - 2-5 Literal Equations and Formulas - Practice and Problem-Solving Exercises: 45

Answer

$n=(2m-3)/(-6)$

Work Step by Step

The literal equation made an error when moving the "+3" to the opposite side of the equation. Rather than properly subtracting 3 from both sides of the equation, the "+3" was simply moved from one side of the equation to the other. The correct process would be as such: $2m=-6n+3$ $2m-3=-6n+3-3$ $2m-3=-6n$ $(2m-3)/(-6)=-6n/(-6)$ $(2m-3)/(-6)= n$ Or $n=(2m-3)/(-6)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.